Factors Influencing Adoption of The Diffusion of Instagram Social Media Innovations among Selected Football Clubs in Tanzania - Chille, Felix Joseph; Mollel, Amanda Blasius (Indonesian Journal of Social Research (IJSR), 2024)
The study aimed to determine the adoption of the diffusion of Instagram social media innovations among selected football clubs in Tanzania. The diffusion of innovation theory guided this study to answer the studied objectives. There needs to be more studies that assess the factors influencing the adoption of the diffusion of social media innovations in the Tanzanian context, which are guided by the diffusion of innovation theory, particularly on the relative advantage, compatibility, and trialability. A survey strategy was utilized in data collection by administering the questionnaires. A sample of 90 respondents was drawn from the study population. Quantitative data was analyzed based on descriptive statistical analysis and multiple linear regression Analysis. The variables under the study were Relative advantage, compatibility, and trialability. In contrast, the dependent variable was the adoption of the diffusion of Instagram social media innovations among selected football clubs in Tanzania. The findings showed that Relative advantage and compatibility affect the adoption of the diffusion of Instagram social media innovations among selected football clubs in Tanzania, while trialability has no effect. This study has unveiled the knowledge contribution by validating the Diffusion of Innovation Theory (DOI), specifically on the Instagram social media platform, by suggesting the relationship between variables under the study by approving or disapproving the theory. The findings will have practical implications that can be applied in real-world contexts to technology adoption.